2011
DOI: 10.1099/jmm.0.020842-0
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic resistance patterns of intestinal Escherichia coli isolates from Nicaraguan children

Abstract: In developing countries, diarrhoeal diseases are one of the major causes of death in children under 5 years of age. It is known that diarrhoeagenic Escherichia coli (DEC) is an important aetiological agent of infantile diarrhoea in Nicaragua. However, there are no recent studies on antimicrobial resistance among intestinal E. coli isolates in Nicaraguan children. The aim of the present study was to determine the antimicrobial resistance pattern in a collection of 727 intestinal E. coli isolates from the faeces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
24
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 37 publications
(43 reference statements)
9
24
4
Order By: Relevance
“…The majority of the multidrugresistant strains were identified in children Ͻ5 years old; this may be caused by the higher prevalence of EAEC in this age group and by colonization rather than infection, leading to a long-term carrier state, which may facilitate antibiotic pressure. This statement is supported by another study investigating ESBL production by EAEC strains, which was detected in 1.5% of children with diarrhea and in 4.3% of children without diarrhea (determined by PCR targeting the CTX-M enzyme) (108). This study was performed in 2008 to 2009 in Nicaragua, and EAEC strains were found to have levels of resistance to ampicillin and trimethoprimsulfamethoxazole that were significantly higher than those of EHEC and EPEC strains (P Ͻ 0.005) and to have higher levels of resistance to amoxicillin than ETEC strains (P ϭ 0.021).…”
Section: Multidrug Resistance In Eaec Strainssupporting
confidence: 54%
See 1 more Smart Citation
“…The majority of the multidrugresistant strains were identified in children Ͻ5 years old; this may be caused by the higher prevalence of EAEC in this age group and by colonization rather than infection, leading to a long-term carrier state, which may facilitate antibiotic pressure. This statement is supported by another study investigating ESBL production by EAEC strains, which was detected in 1.5% of children with diarrhea and in 4.3% of children without diarrhea (determined by PCR targeting the CTX-M enzyme) (108). This study was performed in 2008 to 2009 in Nicaragua, and EAEC strains were found to have levels of resistance to ampicillin and trimethoprimsulfamethoxazole that were significantly higher than those of EHEC and EPEC strains (P Ͻ 0.005) and to have higher levels of resistance to amoxicillin than ETEC strains (P ϭ 0.021).…”
Section: Multidrug Resistance In Eaec Strainssupporting
confidence: 54%
“…In addition, extended-spectrum beta-lactamase (ESBL) production and increased resistance to quinolones in EAEC strains have been described (108,(115)(116)(117). A study conducted in southern India (118) investigated 64 EAEC strains and reported that 75% of the strains were multidrug resistant, and resistance to ciprofloxacin was found in 63.5% of the strains.…”
Section: Multidrug Resistance In Eaec Strainsmentioning
confidence: 99%
“…Similar studies from China [48] and Nicaragua [49] have shown the trend in emergence of multidrug-resistant strains. Chen et al [48] investigated 347 DEC isolates from southeast China and found the multidrug resistance phenotype for 70.2%; in addition, 91.8% of these strains from Chinese patients were resistant to ampicillin, which was higher than the rate reported from the Nicaraguan study (67.7%) [49] and the Iranian study (62.0%) [50]. The Nicaraguan and Iranian studies also showed similar resistance rates for tetracycline and trimethoprim-sulfamethoxazole (>50%).…”
Section: Antimicrobial Resistance Of Eaecmentioning
confidence: 73%
“…For example, the clinical EAEC isolates show a higher resistance in general to the most commonly used antibiotics compared to the other DECs [48,49,51]. In a Peruvian study of infectious diarrhea in infants, EAEC was found to be the most common DEC, and that it had significantly higher resistance to ampicillin, cotrimoxazole, tetracycline and nalidixic acid than the ETEC and EPEC isolates examined from the study population [7,52].…”
Section: Antimicrobial Resistance Of Eaecmentioning
confidence: 92%
“…We previously reported that 36.8% of the aggR gene-positive EAEC strains isolated from diarrheal children in Kagoshima, Japan, were cefotaxime resistant (22), suggesting ESBL production. Subsequently, some CTX-M-producing EAEC strains were reported worldwide (23)(24)(25)(26), including an EAEC-Shiga toxin-producing E. coli (STEC) hybrid clone of O104:H4 that caused a large outbreak in Germany in 2011 (27).…”
mentioning
confidence: 99%